1992
DOI: 10.1002/jcb.240480411
|View full text |Cite
|
Sign up to set email alerts
|

1α,25‐Dihydroxyvitamin D3 modulation in lipid metabolism in established bone marrow‐derived stromal cells, MC3T3‐G2/PA6

Abstract: MC3T3-G2/PA6 (PA6) cells established from newborn mouse calvaria are preadipocytic stromal cells, which differentiate into adipocytes in response to glucocorticoids. We examined the effects of 1 alpha,25-dihydroxyvitamin D3[1 alpha,25(OH)2D3] on adipogenesis in PA6 cells. When PA6 cells were cultured with 10(-8) M dexamethasone, adipocytes containing oil red O-positive droplets first appeared on day 7 (3 days after confluence was attained) and the maximal synthesis of neutral lipids occurred on day 12. Simulta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Primary mouse BM-MSCs also presented a reduced expression of adipsin and AP2 in response to calcitriol [94,95]. Reduced lipid accumulation was presented in response to calcitriol in ST2 and PA6 cells [96,97]. In turn, Kelly et al revealed that calcitriol significantly suppressed glucocorticoid-or thiazolidinedionestimulated adipogenesis and inhibited the expression of adipsin and AP2 without an effect on LPL expression in BMS2 cells [95].…”
Section: The Action Of Vitamin D In the Process Of Adipogenesis-in Vi...mentioning
confidence: 99%
“…Primary mouse BM-MSCs also presented a reduced expression of adipsin and AP2 in response to calcitriol [94,95]. Reduced lipid accumulation was presented in response to calcitriol in ST2 and PA6 cells [96,97]. In turn, Kelly et al revealed that calcitriol significantly suppressed glucocorticoid-or thiazolidinedionestimulated adipogenesis and inhibited the expression of adipsin and AP2 without an effect on LPL expression in BMS2 cells [95].…”
Section: The Action Of Vitamin D In the Process Of Adipogenesis-in Vi...mentioning
confidence: 99%
“…In addition, 1,25(OH) 2 D in 3T3‐L1 can increase the expression of the eight‐twenty‐one protein (ETO/MTG8), which inhibits adipogenesis through repression of C/EBPβ and inhibition of PPARγ 80 . Inhibition of adipogenesis has also been reported in mouse brown adipocytes 64 and in bone marrow cell lines 81,82 . Nevertheless, adipogenic stimulatory effect of 1,25(OH) 2 D has also been shown in 3T3‐L1 cells 83 and in mouse primary preadipocytes, 29 and unliganded VDR seems to be required for adipogenic programming 80 .…”
Section: Biological Effects Of Vd On Adipocytes and Adipose Tissuementioning
confidence: 99%
“…80 Inhibition of adipogenesis has also been reported in mouse brown adipocytes 64 and in bone marrow cell lines. 81,82 Nevertheless, adipogenic stimulatory effect of 1,25(OH) 2 D has also been shown in 3T3-L1 cells 83 and in mouse primary preadipocytes, 29 and unliganded VDR seems to be required for adipogenic programming. 80 Note that the studies with VDR À/À mice reported a reduction of adipose tissue, 67,68 suggesting that adipogenesis could be impacted.…”
Section: Effect Of Vd or Its Metabolites On The Control Of Adipogenesismentioning
confidence: 99%
“…The factors regulating differentiation of marrow stromal precursors into one or the other of these pathways are not well understood and almost nothing is known about this regulation in humans. Although regulation has been studied in vitro using rodent marrow stromal cells and preosteoblastic 9–13 or preadipocytic 14–16 cell lines, it is difficult to generalize from these data because of species differences with human cells and because most of these cell lines were already committed to either the osteoblast or the adipocyte differentiation pathways. Thus, the lack of a model system for uncommitted human marrow stromal (hMS) cells that is capable of differentiating into either the osteoblast or the adipocyte pathway has been a major barrier to defining regulation of this reciprocal process.…”
Section: Introductionmentioning
confidence: 99%